Growth in mouse peritoneal macrophages of Yersinia pestis lacking established virulence determinants. - Straley, S C (1984)
Cultured mouse resident peritoneal macrophages were challenged with strains of Yersinia pestis differing only with respect to the absence of one or more of the virulence determinants established for the species. Guanine-auxotrophic (Pur-) yersiniae were unable to survive within the macrophages; exogenous hypoxanthine and guanosine permitted intracellular growth. This finding supports the idea that Pur- yersiniae are avirulent due to inability to obtain sufficient free purines in host tissues for growth and maintenance and indicates that net biosynthesis is necessary to counteract the intracellular microbicidal environment of macrophages. Yersiniae unable to pigment in medium containing the dye Congo red (Pgm-) or lacking either of the plasmids associated with the pesticin or calcium dependence virulence determinants (Pst- and Vwa-, respectively) were taken up as efficiently into macrophages and grew as well within these cells as did bacteria having all invasive virulence determinants intact. Opsonization with 100% homologous normal serum before infection of macrophages did not affect the ability of Pgm- or Vwa- Pgm- yersiniae to grow within macrophages. Accordingly, attributes independent of these virulence determinants mediate the survival and growth of yersiniae in serum and within resident macrophages, and components of the mammalian environment other than serum and macrophages must interact with Pgm-, Pst- and Vwa- yersiniae to cause their avirulence in vivo.